Adverse Effects of Proton Pump Inhibitors on Platelet Count: A Case Report and Review of the Literature. (30th April 2018) - Mukherjee, Subhajit; Jana, Tanima; Pan, Jen-Jung
Abstract : Proton pump inhibitors (PPIs) are the most effective and preferred class of drugs used to treat peptic ulcer disease, gastroesophageal reflux disease, and other diseases associated with increased production of gastric acid. PPIs in general have an excellent long-term safety profile and are well-tolerated. However, studies have shown some adverse reactions (e.g., osteoporosis, Clostridium difficile -associated diarrhea, Vitamin B12 and iron deficiency, and acute interstitial nephritis) on long-term PPI use. Thrombocytopenia attributed to use of PPIs has been described in a few case reports and a retrospective study. In this case report, we describe a case of PPI-induced thrombocytopenia. In our patient, thrombocytopenia immediately developed after the initiation of PPI on two separate occasions and resolved after its discontinuation. The strong association found in our case implies the potential role of PPI in causing this rare but serious adverse reaction. Based on this case report and the observation from other studies, a PPI-induced adverse event should be considered as a possible etiology for new-onset idiopathic thrombocytopenia.